2005
DOI: 10.1103/physrevlett.95.130604
|View full text |Cite
|
Sign up to set email alerts
|

Structural Order for One-Scale and Two-Scale Potentials

Abstract: We perform molecular dynamics simulations to investigate the relationship between structural order and water-like dynamic and thermodynamic anomalies in spherically-symmetric potentials having either one or two characteristic length scales. Structural order is characterized by translational and orientational order parameters. We find that (i) dynamic and thermodynamic anomalies exist for both one-scale and two-scale ramp potentials, and (ii) water-like structural order anomalies exist only for the two-scale ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
167
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 25 publications
7
167
0
Order By: Relevance
“…Returning to low and intermediate temperatures, the anomalous increase of self-diffusion coefficient with density (and decrease of structural order) is by no means unique to GC fluid; this behavior has been observed for several waterlike model systems, [17][18][19][20][21][22][23][24][25][26] as for colloidal systems with short-range attractive interactions. [42] An important difference however, is that for these systems the anomalous structural and dynamical behavior is observed for a limited density range only, after which the system reverts to normal behavior.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Returning to low and intermediate temperatures, the anomalous increase of self-diffusion coefficient with density (and decrease of structural order) is by no means unique to GC fluid; this behavior has been observed for several waterlike model systems, [17][18][19][20][21][22][23][24][25][26] as for colloidal systems with short-range attractive interactions. [42] An important difference however, is that for these systems the anomalous structural and dynamical behavior is observed for a limited density range only, after which the system reverts to normal behavior.…”
Section: Resultsmentioning
confidence: 97%
“…[13,15] As such, both thermodynamic [3,16] and dynamic [5][6][7][8][9][10][11] properties of GC fluids and binary mixtures have been extensively studied. It has been found that their transport coefficients exhibit anomalous behavior strongly reminiscent of waterlike model systems [17][18][19][20][21][22][23][24][25][26], with diffusivity increasing and viscosity decreasing with density over a certain range of thermodynamic conditions. Furthermore, a strong correlation between this behavior and structural anomalies quantified via excess entropy has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, to describe the quantitative changes in structure of hydration water, Kumar et al calculated the local tetrahedral-order parameter Q [67][68][69][70] for hydration water surrounding lysozyme and DNA. Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…In the case of tetrahedral liquids, the local geometry at low and high densities is tetrahedral and icosahedral respectively and therefore there is a density-driven breakdown of the correlation between q tet and τ . Figure 4 illustrates how S 2 shifts from being negatively correlated with q tet /q ico in the anomalous regime to positively correlated in the normal regime along various isotherms as a consequence of the changing relationship between translational and orientational order.It is useful to apply the above arguments to the one-scale ramp (1SRP) liquid with σ 0 = 0 which displays density and diffusional anomalies but not the structural anomaly since q ico (ρ) does not have a maximum [10]. The 2SRP and 1SRP liquids show the same qualitative behaviour in τ and S 2 with an effective second length scale originating from a peak in g(r) close to zero at intermediate and high densities.…”
mentioning
confidence: 99%
“…Experiments as well as simulations suggest that the anomalous thermodynamic and kinetic properties of water are due to the fluctuating, three-dimensional, locally tetrahedral hydrogen-bonded network. Water-like anomalies are seen in other tetrahedral network-forming liquids, such as silica, as well as in model liquids with isotropic core-softened or two-scale pair potentials [3,4,5,6,7,8,9,10,11].In the case of liquids such as water and silica, a quantitative connection between the structure of the tetrahedral network and the macroscopic density or temperature variables can be made by introducing order metrics to gauge the type as well as the extent of structural order [6,7]. The local tetrahedral order parameter, q tet , associated with an atom i (e.g.…”
mentioning
confidence: 99%